Предмет: Математика,
автор: Настя9949
Доказать что значение выражения не зависит от значения переменной
0,5х+1/7х+7,4-9/14х
решите
Ответы
Автор ответа:
0
0,5х + 1/7х + 7,4 - 9/14х = 1/2х + 1/7х + 7,4 - 9/14х = х * (1/2 + 1/7 - 9/14) + 7,4 = х * (1 * 7 - 1 * 2 - 9 * 1)/14 + 7,4 = х * (7 - 2 - 9)/14 + 7,4 = х * (-4/14) + 7,4 = -2/7х + 7,4.
Похожие вопросы
Предмет: Английский язык,
автор: Настя23455661212
Предмет: Алгебра,
автор: QwertyLokom2
Предмет: Математика,
автор: AzhTweeet
Предмет: Алгебра,
автор: Amperyt
Предмет: Алгебра,
автор: Amperyt